Cloning of the copper-inducible metallothionein (cmt) promoter from Neurospora crassa. - J. Ohrnberger; R. A. Akins (Fungal Genetics Reports, 1995)
There are only a limited number of vectors with inducible promoters that are convenient for in vivo expression in Neurospora crassa. Promoters have been identified and cloned that are induced with blue-light (bli-4; Pietschmann et al 1991 Fungal Genetics Newsl. 38:85-6) or by quinic acid (qa-2; Campbell et al 1994 Fungal Genetics Newsl. 41:20-1). Constitutive promoters have also been used, derived from the beta-tubulin gene bml (Nakano et al 1993 Fungal Genetics Newsl. 40:54-6). The glucose-repressible promoter of grg-1 has also been used (Nakano ibid; Pall and Brunelli 1994 Fungal Genetics Newsl. 41:63-4). The promoter of the N. crassa copper metallothionein gene (cmt) is capable of induction levels of at least 100-fold (Munger et al. 1987 J. Biol. Chem. 262:7363-7) and has been used to express tyrosinase and laccase (Kupper et al. 1990 Curr. Genet. 18:331-5; Schilling et al. 1992 Curr. Genet. 22:197-203).